Workshop cluster 1+γδ T‐cell receptor+ T cells from calves express high levels of interferon‐γ in response to stimulation with interleukin‐12 and ‐18 - Price, Sally J.; Sopp, Paul; Howard, Christopher J.; Hope, Jayne C. (Immunology, 2007)
Summary γδ T‐cell receptor+ T lymphocytes are an important element of the innate immune system. Early production of interferon (IFN)‐γ by γδ T cells may have a role in linking innate and adaptive immune responses and contribute to T helper‐1 bias. We investigated the role of cytokines in the activation and induction of IFN‐γ secretion by bovine workshop cluster 1+ (WC1+) γδ T cells. The effects of culture with interleukin (IL)‐12, IL‐18, IL‐15 and IL‐2 were investigated; these cytokines are known to influence murine and human γδ T cells. We report that bovine WC1+γδ T cells are synergistically stimulated by IL‐12 and IL‐18 to secrete large quantities of IFN‐γ. Neonatal calves were shown to have significantly higher numbers of circulating WC1+γδ T cells than adult animals. In addition, the response of peripheral blood WC1+γδ T cells was significantly higher in neonatal calves compared with adult animals. However, in adult animals the response of lymph node WC1+γδ T cells to IL‐12/IL‐18 was more pronounced than that of peripheral blood WC1+γδ T cells. We hypothesize that the induction of IFN‐γ secretion from WC1+γδ T cells by IL‐12 and IL‐18 is likely to be an important element of the innate response to pathogens such as Mycobacterium bovis. The high numbers of WC1+γδ T cells in neonatal calves, and their inherent ability to respond to inflammatory cytokines, could be a key factor in the enhanced responses seen in calves to BCG vaccination.